Perbedaan Kapasitas Vital Paru Dan Kapasitas Vital Paksa Antara Qori' Dan Non Qori' Di Universitas Muhammadiyah Surakarta - ASY-SYIFA, SHOFIYAH, Isnaini Herawati, SST.FT, S.Pd, M.Sc (2017)
Background: Ijma' of the Islamic scholars define that there is a standard method in reading the Qur'an called qiro'ah that attributed to the previous Imams of qurra'. While qori' is a term for those who do qiro'ah, where qiro'ah itself has difficulty in breathing rate than the reading of the Qur'an in common. Research purposes: to know the differences in vital capacity and forced vital capacity between qori' and non qori' at Muhammadiyah University of Surakarta. Research benefit: to be able to know the differences in vital capacity and forced vital capacity between qori' and non qori' at Muhammadiyah University of Surakarta. Research method: this research is an observational research with cross sectional approach. The sampling technique used is purposive sampling with 30 samples. The measurement of vital capacity and forced vital capacity uses spirometer and mouthpieces, while to know the respondents are qori' or non qori' uses questionnaire. The differences test uses t-test independent with 95% degree of confident. 2 Research findings: Based on the results of independent t-test known that p-value 0.000 < 0.05 for lung vital capacity and forced vital capacity of men, then H0 rejected and Hα accepted. While the results of independent t-test for lung vital capacity and forced vital capacity of women with a p-value 0.008 <0.05 and p-value 0.011 < 0.05, then H0 is rejected and Hα accepted. So that it can be interpreted that there is a difference in lung vital capacity and forced vital capacity between qori 'and non qori' at Muhammadiyah University of Surakarta. Conclusion: There are differences in vital capacity and forced vital capacity between qori' and non qori' at Muhammadiyah University of Surakarta.